Registrars’ perspectives towards virtual teaching in an academic department during the COVID-19 pandemic - Mpemnyama, Lerato Nomonde (University of the Witwatersrand, Johannesburg, 2022)
Background The COVID-19 pandemic brought about unprecedented times that resulted in measures of social distancing that had to be put in place. The Department of Anaesthesiology at the University of Witwatersrand had to comply with these regulations and switched the teaching of registrars from in-person format to a virtual platform. The study aimed to look at the perceptions registrars had towards virtual teaching during the COVID-19 pandemic. Methods This cross-sectional quantitative study was conducted in the Department of Anaesthesiology at the University of Witwatersrand via an online self-administered questionnaire that was distributed to the registrars registered in the department. The validated questionnaire that was used was developed following a literature search and an adaptation from two validated questionnaires. The study was conducted from December 2021 to February 2022. Results The department has a total of 100 registrars, and the response rate was 90%. The study highlighted that virtual teaching did have a positive impact in teaching in the academic department, with 91% (n=81) finding virtual teaching to be effective and 63.9% (n=53) of respondents preferring virtual teaching over in-person teaching. Conclusion The COVID-19 pandemic brought about a disruption to the academic programme in the Department of Anaesthesiology at the University of Witwatersrand, resulting in virtual teaching being implemented. This move has been met with a positive response among the registrars in the department.
A research report submitted in the partial fulfillment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology to the Faculty of Health Sciences, School of Medicine, University of the Witwatersrand, Johannesburg 2022
Keywords: Anaesthesia; COVID-19; Virtual traching; Registrars; Perspectives; UCTD; SDG-4: Quality education